MODEL PENDIDIKAN KEWARGANEGARAAN GLOBAL DI SEKOLAH DASAR BERBASIS MULTIKULTURALISME SEBAGAI PRAKTIK PEMBANGUNAN BERKELANJUTAN DI BIDANG KEMANUSIAAN - Rahmadiyani, Alya; Rahmawati, Ayu; Idris, Aceng Fahmi; Nanggala, Agil (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
Global Citizenship Education in Elementary Schools is a science that shapes students into competent global citizens, by developing dimensions of global competence such as knowledge, skills and character. The implementation of citizenship education in elementary schools needs to instill Global Citizenship education based on multiculturalism in order to be able to maintain the existence of PKN in the global land and help optimize the process of sustainable development in the humanitarian field. The purpose of this study is to develop a model of global citizenship education based on multiculturalism in elementary schools. This study uses a qualitative approach with a literature study method from various sources such as scientific journals, articles and other sources relevant to the research topic. The researcher conducted a reflection and finalization analysis of the Global Civics model based on Multiculturalism as a Sustainable Development Practice in the Humanitarian Field. The data obtained were narrated and described to obtain comprehensive results. The data shows that there are five stages consisting of relevance, core realization, reflection and massive socialization. This stage is carried out as an application of the global Citizenship Education model in elementary schools as a sustainable development practice in the humanitarian field.